Preparation method of large dissimilar material composite structural body

By designing the shape size of the outer ring and the inner core structure in the large -scale alien material composite structure, the heat expansion coefficient difference is controlled to control the welding gap, which solves the problem of excessive amount of the material, and achieves high -quality connection and cost reduction.

CN119368849APending Publication Date: 2025-01-28SHANGHAI INSTITUTE OF APPLIED PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411516338.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

There is too much brazing solder material used in the preparation of existing large exotic material composite structures, which leads to high costs and makes it difficult to achieve high-quality connections and cost control.

Method used

By designing the shape size of the outer ring structure and the inner core structure, it has a different diameter relationship at room temperature and welding temperature. The difference in thermal expansion coefficient is used to control the welding gap at high temperature to reduce the amount of pantomy.

Benefits of technology

Under the premise of ensuring the quality of the welded welding, the amount of raw material is greatly reduced, the cost is reduced, and the window of the process parameters is broaden to ensure the quality of the welding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368849A_ABST
    Figure CN119368849A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a large dissimilar material composite structural body. The large dissimilar material composite structural body is formed by connecting a metal outer ring structural body and a non-metal inner core structural body embedded in an inner ring of the outer ring structural body, and the thermal expansion coefficient of the metal material is larger than that of the non-metal material. The preparation method comprises the steps that 1, the inner wall face of the outer ring structural body and the outer wall face of the inner core structural body are machined into inclined faces with the same taper angle; 2, carrying out metallization treatment on the outer wall surface of the inner core structure; 3, the metalized inner core structural body is hoisted into the outer ring structural body at the normal temperature, and the bottom face of the inner core structural body is located between the lower end face of the outer ring structural body and the upper end face of the outer ring structural body after assembly is completed; and 4, the assembled structural body is brazed. Compared with the prior art, on the premise that the brazing connection quality is guaranteed, the used brazing amount can be greatly reduced, and the cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a large-scale heterogeneous material composite structure, belonging to the technical field of brazing. Background Art

[0002] The hard X-ray free electron laser device is a high-energy, high-power radiation device and a major national scientific and technological infrastructure project. During its operation, it will generate a strong electron beam current. The electron beam used to generate the free electron laser will eventually be collected by the electron beam collection bucket set at the end of each beam line segment and no longer used. The electron beam collection bucket must not only collect almost all of the electron beam energy, but also quickly and effectively remove the heat of the electrons in the collection bucket. It is required that the electron beam collection bucket can operate stably and normally for a long time under the continuous bombardment of the high-power beam.

[0003] The main structure for collecting electron beams and taking away heat is the absorber, which is a cylindrical structure formed by connecting a cylindrical graphite core and a copper ring. At present, the connection between large graphite and copper of this type is mainly mechanical connection and brazing connection. Mechanical connection makes it difficult to effectively and quickly remove the heat collected by the graphite beam due to the air thermal resistance. Therefore, the brazing connection method of graphite and copper has more application prospects.

[0004] The existing graphite and copper brazing connection technologies mainly fall into the following categories: (1) Brazing of small structural parts: For example, Song Xiaoguo and other scholars used SnAgCuTi to metalize graphite for graphite-copper composite structure commutator, and then applied a certain pressure to complete the connection between graphite and copper at low temperature. This low-temperature brazing technology has achieved good results, but it is not suitable for components running at high temperatures; Liu Yanwei, Zou Guisheng and other scholars used AgCuTi to directly braze graphite and copper. The size of the brazed specimens was extremely small, and the main connection area was 25×25mm, or Φ8mm; (2) Brazing of large structural parts: For example, Yang Hao and other scholars provided a large-size graphite / copper brazing method, using AgCuInTi to metalize graphite, and then using tantalum or niobium as an intermediate layer to achieve the connection between copper and graphite. However, this method is mainly suitable for brazing in flat welding positions, not for brazing in cylindrical vertical welding positions. The applicant of this patent proposed a method for vertically welding large graphite and copper in CN202311618578.9 "Connection method of graphite-copper composite structure and graphite-copper composite structure", which can effectively solve the technical problem of large-area brazing quality. However, as the size of graphite and copper continues to increase, the brazing gap becomes larger, which greatly increases the amount of brazing material required and the brazing cost.

[0005] Therefore, how to achieve high-quality connection of large-scale heterogeneous material composite structures with large circumferential bonding surfaces such as electron beam absorbers while controlling the brazing gap to reduce costs is an urgent problem that technicians in this field need to solve. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the problem of excessive use of brazing filler metal in the preparation process of existing large-scale heterogeneous material composite structures, and to provide a preparation method for large-scale heterogeneous material composite structures, which can greatly reduce the amount of brazing filler metal used and reduce costs while ensuring the quality of brazing connections.

[0007] The present invention specifically adopts the following technical solutions to solve the above technical problems:

[0008] A method for preparing a large-scale heterogeneous material composite structure, wherein the large-scale heterogeneous material composite structure is formed by connecting an outer ring structure of a metal material and an inner core structure of a non-metallic material embedded in an inner ring of the outer ring structure, wherein the thermal expansion coefficient of the metal material is greater than the thermal expansion coefficient of the non-metallic material; the preparation method comprises the following steps:

[0009] Step 1, the inner wall surface of the outer ring structure and the outer wall surface of the inner core structure are respectively processed into inclined surfaces with the same cone angle, so that the diameter of the lower end surface of the inner core structure at room temperature is larger than the inner ring diameter of the lower end surface of the outer ring structure and smaller than the inner ring diameter of the upper end surface of the outer ring structure, and the diameter of the lower end surface of the inner core structure at the brazing temperature is less than or equal to the inner ring diameter of the lower end surface of the outer ring structure;

[0010] Step 2, metallizing the outer wall surface of the inner core structure;

[0011] Step 3: hoist the metallized inner core structure into the outer ring structure at room temperature. After assembly, the bottom surface of the inner core structure is located between the lower end surface of the outer ring structure and the upper end surface of the outer ring structure.

[0012] Step 4: brazing the assembled structure. At the brazing temperature, the inner core structure gradually falls into the outer ring structure and finally the lower end faces of the two are flush. After natural cooling, the brazing connection between the outer ring structure and the inner core structure is achieved to obtain the large heterogeneous material composite structure.

[0013] Preferably, the cone angle is 92°.

[0014] In one of the preferred solutions, the metallization treatment is achieved by coating the outer wall surface of the inner core structure with solder and heating it to above the melting point of the solder in a vacuum environment.

[0015] In a second preferred embodiment, the metallization treatment is achieved by depositing active metal on the outer wall of the inner core structure.

[0016] Preferably, the brazing is performed using a silver-based solder.

[0017] Further preferably, the brazing temperature of the brazing is 830-900° C., and the holding time is not less than 10 minutes.

[0018] Based on the same inventive concept, the following technical solutions can also be obtained:

[0019] A large-scale composite structure of heterogeneous materials, which is composed of an outer ring structure of a metal material and an inner core structure of a non-metallic material embedded in the inner ring of the outer ring structure, wherein the thermal expansion coefficient of the metal material is greater than the thermal expansion coefficient of the non-metallic material; and is prepared by the preparation method described in any of the above technical solutions.

[0020] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0021] The present invention ingeniously designs and assembles the outer dimensions of the inner core structure and the outer ring structure, and utilizes the difference in thermal expansion coefficients of dissimilar materials. During the high-temperature heating process, the gap between the two is continuously enlarged, and graphite continuously falls to fill the gap, so that the final brazing gap can be arbitrarily controlled, which can greatly reduce the amount of brazing material used and reduce costs, and provide a more economical solution for the brazing of large dissimilar materials.

[0022] In the present invention, since the brazing gap is controllable, the thickness of the brazing weld can be controlled, so that the degree of reaction between the liquid brazing material and the base material can be better controlled, the window of process parameters is widened, and the brazing quality is more easily ensured;

[0023] The invention has simple process and strong applicability, and can be widely used in the preparation of large heterogeneous material composite structures composed of inner core structures of graphite, ceramic, and carbon-based composite materials and outer ring structures of metal materials such as copper, stainless steel, carbon steel, and nickel-based alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the principle of the technical solution of the present invention;

[0025] Figure 2 Schematic diagram of the process of the method of the present invention, wherein (a) is the structure before brazing, and (b) is the structure after brazing. DETAILED DESCRIPTION

[0026] In view of the problem of excessive use of brazing filler metal and high cost in the prior art, the present invention proposes the following solutions:

[0027] A method for preparing a large-scale heterogeneous material composite structure, wherein the large-scale heterogeneous material composite structure is formed by connecting an outer ring structure of a metal material and an inner core structure of a non-metallic material embedded in an inner ring of the outer ring structure, wherein the thermal expansion coefficient of the metal material is greater than the thermal expansion coefficient of the non-metallic material; the preparation method comprises the following steps:

[0028] Step 1, the inner wall surface of the outer ring structure and the outer wall surface of the inner core structure are respectively processed into inclined surfaces with the same cone angle, so that the diameter of the lower end surface of the inner core structure at room temperature is larger than the inner ring diameter of the lower end surface of the outer ring structure and smaller than the inner ring diameter of the upper end surface of the outer ring structure, and the diameter of the lower end surface of the inner core structure at the brazing temperature is less than or equal to the inner ring diameter of the lower end surface of the outer ring structure;

[0029] Step 2, metallizing the outer wall surface of the inner core structure;

[0030] Step 3: hoist the metallized inner core structure into the outer ring structure at room temperature. After assembly, the bottom surface of the inner core structure is located between the lower end surface of the outer ring structure and the upper end surface of the outer ring structure.

[0031] Step 4: brazing the assembled structure. At the brazing temperature, the inner core structure gradually falls into the outer ring structure and finally the lower end faces of the two are flush. After natural cooling, the brazing connection between the outer ring structure and the inner core structure is achieved to obtain the large heterogeneous material composite structure.

[0032] In the traditional preparation process of large heterogeneous material composite structures such as electron beam absorbers, the outer wall of the inner core structure and the inner ring wall of the outer ring structure are both perpendicular to the bottom surface, without using an inclined surface structure. Usually, a 0.1mm-2mm assembly gap is left between the two. Even if there is no gap between the outer wall of the inner core and the inner wall of the outer ring at room temperature, due to the difference in thermal expansion coefficients between the inner core and the outer ring, when the temperature rises to the brazing temperature, the width W of the brazing gap to be filled with brazing filler metal has the following relationship: W = α 外环 ×r×(T 钎焊 -T 室温 )-α 内芯 ×r×(T 钎焊 -T 室温 ), where α 外环 and α 内芯 They represent the thermal expansion coefficients of the outer ring and the inner core from room temperature to the brazing temperature, r represents the radius of the bottom circle, and W is a constant after the materials of the inner core and the outer ring and the brazing temperature are determined.

[0033] The inner wall surface of the outer ring structure and the outer wall surface of the inner core structure are respectively processed into inclined surfaces with the same cone angle θ, and the diameter of the lower end surface of the inner core structure at room temperature is larger than the inner ring diameter of the lower end surface of the outer ring structure and smaller than the inner ring diameter of the upper end surface of the outer ring structure, and when the diameter of the lower end surface of the inner core structure at the brazing temperature is less than or equal to the inner ring diameter of the lower end surface of the outer ring structure, as Figure 1 As shown, the gap G has the following relationship with the height D and the taper angle θ: G=D×tan(θ-90°). Due to the existence of the gap G, the width W' of the brazing gap that needs to be filled with solder is reduced to W'=WG. When the taper is determined, the brazing gap of the dissimilar material structure can be adjusted arbitrarily by changing the height D, which can greatly reduce the amount of solder used, thereby greatly reducing the brazing cost.

[0034] Preferably, the cone angle is 92°.

[0035] The metallization treatment can be achieved by various existing technologies, for example, by coating the outer wall of the inner core structure with solder and heating it to above the melting point of the solder in a vacuum environment; or by depositing active metal on the outer wall of the inner core structure.

[0036] The brazing can select various types of appropriate solders according to the type of base material. Considering the advantages of silver-based solders over other solders, such as excellent wetting performance, strong gap filling ability, and excellent thermal conductivity, the present invention preferably uses silver-based solders such as AgCuTi, AgCu, AgCuZn, AgCuZnSn, and AgCuZnCd for the brazing. Further preferably, the brazing temperature of the brazing is 830-900°C, and the holding time is not less than 10 minutes.

[0037] In order to facilitate public understanding, the technical solution and technical effects of the present invention are described in detail below through several specific embodiments and in conjunction with the accompanying drawings:

[0038] Embodiment 1:

[0039] In this embodiment, the inner core structure of the large heterogeneous material composite structure is made of graphite, and the outer ring structure is made of copper; the specific preparation process is as follows:

[0040] Step 1: Figure 2 As shown in (a), the inner wall surface of the copper outer ring structure and the outer wall surface of the graphite inner core structure are respectively processed into inclined surfaces with the same cone angle θ=92°, so that the diameter of the lower end surface of the graphite inner core structure at room temperature is larger than the inner ring diameter of the lower end surface of the copper outer ring structure and smaller than the inner ring diameter of the upper end surface of the copper outer ring structure, and the diameter of the lower end surface of the graphite inner core structure at the brazing temperature is less than or equal to the inner ring diameter of the lower end surface of the copper outer ring structure;

[0041] Step 2: Apply AgCuTi solder paste on the outer wall of the graphite core structure. -2 ~10 -4 Heat to 800-900°C in a Pa vacuum environment, keep warm for 10-60 minutes, cool to room temperature and take out to complete graphite metallization;

[0042] Step 3: Figure 2 As shown in (a), the metallized graphite inner core structure is hoisted into the copper outer ring structure. After the assembly is completed, the bottom surface of the graphite inner core structure is higher than the bottom surface of the copper outer ring structure by D=50mm;

[0043] Step 4: Add AgCuTi solder or other silver-based solder to the pre-processed groove on the upper end surface of the copper outer ring structure; heat the assembled structure to 830-900°C in a vacuum environment and keep it warm for not less than 10 minutes. The graphite inner core structure gradually falls into the copper outer ring structure during the heating process and finally achieves the flushing of the lower end surfaces of the two, filling the gap G=1.746mm between the graphite inner core structure and the copper outer ring structure. After cooling, the brazing connection of the large graphite-copper structure is completed. Figure 2 As shown in (b) in .

[0044] In this embodiment, the brazing gap to be filled with brazing filler metal is 0.8 mm. Compared with the conventional graphite and copper solution without taper angle, the amount of brazing filler metal required is reduced by more than two-thirds.

[0045] Embodiment 2:

[0046] In this embodiment, the inner core structure of the large heterogeneous material composite structure is made of graphite, and the outer ring structure is made of copper; the specific preparation process is as follows:

[0047] Step 1: Figure 2 As shown in (a), the inner wall surface of the copper outer ring structure and the outer wall surface of the graphite inner core structure are respectively processed into inclined surfaces with the same cone angle θ=92°, so that the diameter of the lower end surface of the graphite inner core structure at room temperature is larger than the inner ring diameter of the lower end surface of the copper outer ring structure and smaller than the inner ring diameter of the upper end surface of the copper outer ring structure, and the diameter of the lower end surface of the graphite inner core structure at the brazing temperature is less than or equal to the inner ring diameter of the lower end surface of the copper outer ring structure;

[0048] Step 2: Apply AgCuTi solder paste on the outer wall of the graphite core structure. -2 ~10 -4 Heat to 800-900°C in a Pa vacuum environment, keep warm for 10-60 minutes, cool to room temperature and take out to complete graphite metallization;

[0049] Step 3: Figure 2As shown in (a), the metallized graphite inner core structure is hoisted into the copper outer ring structure. After the assembly is completed, the bottom surface of the graphite inner core structure is higher than the bottom surface of the copper outer ring structure by D=100mm;

[0050] Step 4. Since the graphite metallization in this embodiment uses solder and the size of D is relatively large, no solder is added in this step, but the AgCuTi metallization layer on the outer wall of the graphite inner core structure is directly used as the solder; the assembled structure is heated to 830-900°C in a vacuum environment and kept warm for not less than 10 minutes. The graphite inner core structure gradually falls into the copper outer ring structure during the heating process and finally the lower end faces of the two are flush, filling the gap G=3.49mm between the graphite inner core structure and the copper outer ring structure. After cooling, the brazing connection of the large graphite-copper structure is completed, such as Figure 2 As shown in (b) in .

[0051] In this embodiment, the brazing gap to be filled with brazing filler is -0.8 mm. Compared with the conventional graphite and copper solution without taper angle, the amount of brazing filler required is greatly reduced, and since no additional brazing filler is added during the brazing process, the process is simplified.

[0052] Embodiment three:

[0053] In this embodiment, the inner core structure of the large heterogeneous material composite structure is made of alumina ceramic, and the outer ring structure is made of stainless steel; the specific preparation process is as follows:

[0054] Step 1: Figure 2 As shown in (a), the inner wall surface of the stainless steel outer ring structure and the outer wall surface of the alumina ceramic inner core structure are respectively processed into inclined surfaces with the same cone angle θ=92°, so that the lower end surface diameter of the alumina ceramic inner core structure at room temperature is larger than the inner ring diameter of the lower end surface of the stainless steel outer ring structure and smaller than the inner ring diameter of the upper end surface of the stainless steel outer ring structure, and the lower end surface diameter of the alumina ceramic inner core structure at the brazing temperature is less than or equal to the inner ring diameter of the lower end surface of the stainless steel outer ring structure;

[0055] Step 2: The outer wall of the alumina ceramic inner core structure is plated with Cr or Ti by a vapor deposition process to complete the metallization of the alumina ceramic;

[0056] Step 3: Figure 2 As shown in (a), the metallized alumina ceramic inner core structure is hoisted into the stainless steel outer ring structure. After the assembly is completed, the bottom surface of the alumina ceramic inner core structure is higher than the bottom surface of the stainless steel outer ring structure by D=50mm;

[0057] Step 4: Add AgCuTi brazing filler metal or other silver-based brazing filler metal to the pre-processed groove on the upper end surface of the stainless steel outer ring structure; heat the assembled structure to 830-900°C in a vacuum environment and keep it warm for not less than 10 minutes. The alumina ceramic inner core structure gradually falls into the stainless steel outer ring structure during the heating process and finally the lower end surfaces of the two are flush, filling the gap G=1.179mm between the stainless steel outer ring structure and the alumina ceramic inner core structure. After cooling, the brazing connection of the large alumina ceramic-stainless steel structure is completed. Figure 2 As shown in (b) in .

[0058] In this embodiment, the brazing gap to be filled with brazing filler metal is 0.3 mm. Compared with the conventional solution of alumina ceramic and stainless steel without a taper angle, the amount of brazing filler metal required is reduced by more than two-thirds.

[0059] Embodiment 4:

[0060] In this embodiment, the inner core structure of the large heterogeneous material composite structure is made of silicon carbide ceramics, and the outer ring structure is made of nickel-based alloy; the specific preparation process is as follows:

[0061] Step 1: Figure 2 As shown in (a), the inner wall surface of the nickel-based alloy outer ring structure and the outer wall surface of the silicon carbide ceramic inner core structure are respectively processed into inclined surfaces with the same cone angle θ=92°, so that the lower end surface diameter of the silicon carbide ceramic inner core structure at room temperature is larger than the inner ring diameter of the lower end surface of the nickel-based alloy outer ring structure and smaller than the inner ring diameter of the upper end surface of the nickel-based alloy outer ring structure, and the lower end surface diameter of the silicon carbide ceramic inner core structure at the brazing temperature is less than or equal to the inner ring diameter of the lower end surface of the nickel-based alloy outer ring structure;

[0062] Step 2: The outer wall of the silicon carbide ceramic inner core structure is plated with Zr or Ti by a vapor deposition process to complete the metallization of the silicon carbide ceramic;

[0063] Step 3: Figure 2 As shown in (a), the metallized silicon carbide ceramic inner core structure is hoisted into the nickel-based alloy outer ring structure. After the assembly is completed, the bottom surface of the silicon carbide ceramic inner core structure is higher than the bottom surface of the nickel-based alloy outer ring structure by D=150mm;

[0064] Step 4: Add AgCuTi brazing filler metal or other silver-based brazing filler metal to the pre-processed groove on the upper end surface of the nickel-based alloy outer ring structure; heat the assembled structure to 830-900°C in a vacuum environment and keep it warm for not less than 10 minutes. The silicon carbide ceramic inner core structure gradually falls into the nickel-based alloy outer ring structure during the heating process and finally achieves the flushing of the lower end surfaces of the two, filling the gap G=2.695mm between the nickel-based alloy outer ring structure and the silicon carbide ceramic inner core structure. After cooling, the brazing connection of the large silicon carbide ceramic-nickel-based alloy structure is completed. Figure 2 As shown in (b) in .

[0065] In this embodiment, the brazing gap to be filled with brazing filler metal is 0.1 mm. Compared with the conventional solution of silicon carbide ceramic and nickel-based alloy without taper angle, the amount of brazing filler metal required is reduced by more than two-thirds.

Claims

1. A method for preparing a large-scale heterogeneous material composite structure, wherein the large-scale heterogeneous material composite structure is formed by connecting an outer ring structure of a metal material and an inner core structure of a non-metallic material embedded in the inner ring of the outer ring structure, wherein the thermal expansion coefficient of the metal material is greater than the thermal expansion coefficient of the non-metallic material; characterized in that: The preparation method comprises the following steps: Step 1, the inner wall surface of the outer ring structure and the outer wall surface of the inner core structure are respectively processed into inclined surfaces with the same cone angle, so that the diameter of the lower end surface of the inner core structure at room temperature is larger than the inner ring diameter of the lower end surface of the outer ring structure and smaller than the inner ring diameter of the upper end surface of the outer ring structure, and the diameter of the lower end surface of the inner core structure at the brazing temperature is less than or equal to the inner ring diameter of the lower end surface of the outer ring structure; Step 2, metallizing the outer wall surface of the inner core structure; Step 3: hoist the metallized inner core structure into the outer ring structure at room temperature. After assembly, the bottom surface of the inner core structure is located between the lower end surface of the outer ring structure and the upper end surface of the outer ring structure. Step 4: brazing the assembled structure. At the brazing temperature, the inner core structure gradually falls into the outer ring structure and finally the lower end faces of the two are flush. After natural cooling, the brazing connection between the outer ring structure and the inner core structure is achieved to obtain the large heterogeneous material composite structure.

2. The method for preparing a large-scale heterogeneous material composite structure according to claim 1, characterized in that: The cone angle is 92°.

3. The method for preparing a large-scale heterogeneous material composite structure according to claim 1, characterized in that: The metallization treatment is achieved by coating the outer wall surface of the inner core structure with solder and heating it to a temperature above the melting point of the solder in a vacuum environment.

4. The method for preparing a large-scale heterogeneous material composite structure according to claim 1, characterized in that: The metallization treatment is achieved by depositing active metal on the outer wall of the inner core structure.

5. The method for preparing a large-scale heterogeneous material composite structure according to claim 1, characterized in that: The brazing is performed using a silver-based brazing filler metal.

6. The method for preparing a large-scale heterogeneous material composite structure according to claim 5, characterized in that: The brazing temperature of the brazing is 830-900°C, and the holding time is not less than 10 minutes.

7. A large-scale composite structure of heterogeneous materials, the large-scale composite structure of heterogeneous materials is formed by connecting an outer ring structure of a metal material and an inner core structure of a non-metallic material embedded in the inner ring of the outer ring structure, the thermal expansion coefficient of the metal material is greater than the thermal expansion coefficient of the non-metallic material; characterized in that: The method is prepared by the method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Method for connecting graphite-copper composite structure, and graphite-copper composite structure

    CN117415401A